2000
DOI: 10.1088/0029-5515/40/7/309
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced particle confinement and turbulence reduction due toE Bshear in the TEXTOR tokamak

Abstract: Positive radial electric fields have been created at the edge of the TEXTOR tokamak plasma using an electrode. The electric field induces a thin (δr ∼ 1.5 cm), E × B driven layer at the edge rotating poloidally at 12-20 km/s and featuring high shear. Concomitant changes in the density and poloidal electric field fluctuations and their cross-phase in the shear layer result in suppression of radial turbulent particle transport, even at low radial electric field strength. Temperature fluctuations are reduced, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
84
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(90 citation statements)
references
References 43 publications
6
84
0
Order By: Relevance
“…As noted earlier, tokamak experiments have sometimes shown evidence for an inward turbulent flux that are usually coincident with strong edge pressure gradients and E Â B shear flows found in improved confinement regimes [16][17][18][19] and space plasma observations also indicate up-gradient transport processes with simultaneous density gradient and E Â B shear regions. [4][5][6][7][8] These earlier observations are reminiscent of the results reported here, suggesting similar mechanisms could be at work in both cases (although theory shows magnetic shear to be effective at quenching the linear transverse KH instability 39 ).…”
Section: -2mentioning
confidence: 66%
See 1 more Smart Citation
“…As noted earlier, tokamak experiments have sometimes shown evidence for an inward turbulent flux that are usually coincident with strong edge pressure gradients and E Â B shear flows found in improved confinement regimes [16][17][18][19] and space plasma observations also indicate up-gradient transport processes with simultaneous density gradient and E Â B shear regions. [4][5][6][7][8] These earlier observations are reminiscent of the results reported here, suggesting similar mechanisms could be at work in both cases (although theory shows magnetic shear to be effective at quenching the linear transverse KH instability 39 ).…”
Section: -2mentioning
confidence: 66%
“…[10][11][12][13][14][15] For fusion systems, inferred transport fluxes are often decomposed into an inward-directed turbulent pinch and down-gradient diffusive transport components (both of which are attributed to a combination of density and temperature gradients) that then compete to form the plasma equilibrium. In a few cases, direct measurements of net inward turbulent particle fluxes have been reported during or shortly after the formation of transport barriers associated with the formation of a suitably strong E Â B shear layer [16][17][18][19] or during the application of an externally forced E Â B shear flow. 20 However, the cause of the net inward flux in these latter works was never identified, nor has velocity shear ever been considered as a possible mechanism to drive inward pinches in confinement experiments.…”
mentioning
confidence: 99%
“…1,2 Shear decorrelation of turbulence can and has been shown to occur by mean E ϫ B flows, 3,4 but can also result from time-varying Ẽ ϫ B flows, such as occurring in zonal flows ͑ZFs͒ identified as toroidal and poloidal symmetric potential structures ͑m = n =0͒ with finite radial wavelength. 5 Such ZFs might thus also be important ingredients in regulating turbulence and hence take part in explaining the transition from low to high ͑L-H͒ confinement regimes.…”
Section: Long-distance Correlation and Zonal Flow Structures Induced mentioning
confidence: 99%
“…Details on the biasing H-mode have been described earlier. 3,4,18 Figure 1͑d͒ shows the time trace of the fast probe, which moves from the scrape-off layer ͑SOL͒ into the edge inside the last closed flux surface ͑LCFS͒. Meanwhile the stationary probe stays also inside the LCFS ͑not shown here͒.…”
Section: Long-distance Correlation and Zonal Flow Structures Induced mentioning
confidence: 99%
“…Thus, in the early phase of the ZF the cross phase α nE rather than the turbulent amplitudes is relevant for transport reduction as it was already emphasized in theoretical [34,35] works. Also biasing experiments indicated that shear flows mainly act on the cross phase [36,37,25].…”
mentioning
confidence: 99%